2019
DOI: 10.1002/aoc.4689
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of nitroaromatics to anilines catalyzed by air‐stable arene ruthenium (II)–NNN pincer complexes

Abstract: A series of air‐stable, phosphine‐free arene ruthenium (II)–NNN pincer complexes (RuL, RuL1, RuL2 and RuL3) have been synthesized and characterized by spectroscopic and single‐crystal X‐ray analysis. Further, arene ruthenium (II)–NNN pincer complexes have been used as catalyst for hydrogenation of nitroaromatics into aniline in the presence of NaBH4 at room temperature. The catalytic process suggested highly chemo‐selective nitroreduction with wide functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…UV‐Vis and 1 H NMR spectral experiments confirm that the reduction proceeds through pathway A. In this study, Ru complexes were reacted with NaBH 4 in ethanol, similar to those reported in the literature 28,76,80 . Unfortunately, the intermediate Ru‐H could not be isolated in 1 H NMR.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…UV‐Vis and 1 H NMR spectral experiments confirm that the reduction proceeds through pathway A. In this study, Ru complexes were reacted with NaBH 4 in ethanol, similar to those reported in the literature 28,76,80 . Unfortunately, the intermediate Ru‐H could not be isolated in 1 H NMR.…”
Section: Resultssupporting
confidence: 79%
“…In this study, Ru complexes were reacted with NaBH 4 in ethanol, similar to those reported in the literature. 28,76,80 Unfortunately, the intermediate Ru-H could not be isolated in 1 H NMR. However, in nitro reduction reactions, considering the literature data, 2,28,76,80 we predict that the Ru-H intermediate is formed during the catalytic reaction of the obtained ruthenium complexes.…”
Section: The Mechanistic Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can dramatically promote the catalytic activity applied in borrowing hydrogen catalysis using ligands containing functional groups such as NH [33][34][35][36][37] and OH [38][39][40] . Among them, NNN ligands [41][42][43] bearing NH [44,45] coordinated with Ru metal could be potential chelating ligands due to their synthetic accessibility and excellent air-and moisture-stability compared to phosphine ligands.…”
Section: Introductionmentioning
confidence: 99%